A Package for SMEs. A Second Step Towards a Definitive VAT System in Order to Strengthen the Tax Compliance of the Taxpayer - Rodica Ghiur; Paula Mihailescu Todor Silvia; Petre Brezeanu; Cornel Dumiter Florin; Vizoli Mariana (Studies in Business and Economics, 2020)
In this study we reveal the measures taken by the Council of the European Union in the field of VAT to support SMEs and the reasons that led the Council of the European Union to take these decisions. It is also indicated the general definition of SMEs in European law as it has been taken up by various other authors, as well as the supportive behavior of SMEs that the European Commission has always had. On the other hand, we carried out a study that included variables defining SMEs in three fields of activity from four countries, located territorially in different areas of the European Union and we identified, using statistical correlation, different coefficients of correlation between the value added the number of SMEs, the number of people employed by SMEs, their turnover in that field of activity. The correlation coefficients that indicated a strong / moderate linearity link indicated that the measures taken by the European Union, through the Council and the European Commission, are welcome as the added value in many areas of activity shows a strong correlation with the number of taxable persons, the number employees of those taxable persons and their turnover.